THE APPLICATION OF INDIRECT FEEDBACK TO IMPROVE STUDENTS’ PARAGRAPH WRITING - Mega Mulianing Maharani (EduLite: Journal of English Education, Literature and Culture, 2017)
Writing is one of the important skills should be mastered by students of English education program. Mastering writing forces students to be able to produce good paragraph. Paragraph is said to be good if it is well organized. Organizing good paragraph is the problem faced by the second semester students of English education of Sultan Agung Islamic University. Based on that problem, the writer decided to apply indirect feedback to the students’ paragraph writing. The writer wants to know the way indirect feedback applied to improve the students’ paragraph writing. The writer used action research to come up to the objective of the research. There was one cycle of the research which consisted of planning, acting, observing, and reflecting. The writer adopted the steps of analyzing the data as proposed by Burns (1999) which consisted of assembling, coding, comparing, building meaning and interpretation and reporting the outcomes. The result was that the way the writer used underline to the students’ writing could improve the students’ paragraph writing. The students could provide correct final revision of their inappropriate writing